Pune GSH supplementation study: Analyzing longitudinal changes in type 2 diabetic patients using linear mixed-effects models - Madathil, Arjun Kolappurath; Ghaskadbi, Saroj; Kalamkar, Saurabh; Goel, Pranay (Frontiers in Pharmacology, 2023)
Background: Oral GSH supplementation along with antidiabetic treatment was shown to restore the body stores of GSH significantly and reduce oxidative DNA damage (8-OHdG) of Indian Type 2 diabetic (T2D) patients over six months in our recent clinical study. Post hoc analysis of the data also suggested that elder patients benefit from improved HbA1c and fasting insulin. Methods: We modeled longitudinal changes in diabetic individuals using a linear mixed-effects (LME) framework and obtained (i) the distribution of individual trajectories with and without GSH supplementation and (ii) the overall rates of changes in the different study arms. Serial changes in elder and younger diabetic individuals were also modeled independently to examine differences in their progression. Results: The average linear trajectories obtained from the model explain how biochemical parameters in T2D patients progress over six months on GSH supplementation. Model estimates show improvements in erythrocytic GSH of 108 µM per month and a reduction in 8-OHdG at a rate of 18.5 ng/µg DNA per month in T2D patients. GSH replenishes faster in younger people than in the elder. 8-OHdG reduced more rapidly in the elder (24 ng/µg DNA per month) than in younger (12 ng/µg DNA per month) individuals. Interestingly, elder individuals show a substantial reduction in HbA1c (0.1% per month) and increased fasting insulin (0.6 µU/mL per month). Changes in GSH correlate strongly with changes in HbA1c, 8-OHdG, and fasting insulin in the elder cohort. Conclusions: The model estimates strongly suggest it improves the rate of replenishment in erythrocytic GSH stores and reduces oxidative DNA damage. Elder and younger T2D patients respond differently to GSH supplementation: It improves the rate of reduction in HbA1c and increases fasting insulin in elder patients. These model forecasts have clinical implications that aid in personalizing treatment targets for using oral GSH as adjuvant therapy in diabetes.